Application of FRAC (Financial Ratio Analysis Card) Media to Improve Learning Activities and Learning Outcomes of Students of SMK Tamansiswa 1 Jakarta in Accounting Subjects (Universitas Pamulang, 2025)
This study aims to improve students' learning activities and outcomes through the implementation of the FRAC Smart Card (Financial Ratio Analysis Card) in Accounting subjects at SMK Tamansiswa 1 Jakarta. The research employed a Classroom Action Research (CAR) design, conducted in three cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects were 32 twelfth-grade Accounting students. Research instruments included observation sheets on learning activities, achievement tests, and interviews with teachers and students. The findings indicated a significant improvement in students' learning activities, progressing from a